TALENTED STUDENT, WORKING WITH STUDENTS IN THE PROCESS OF EDUCATION AND IDENTIFYING THEIR TALENTS - Isabayeva Dilfuza Komiljonovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article shows forward a number of views on the importance of the psychological mechanisms of self-development of the gifted child, as well as the formation and implementation of individual talent.